Penerapan Digital Marketing Sebagai Strategi Pemasaran Pada UMKM Pakan Super Klasik - Cindy Clarissa Quenby; Maharani Ikaningtyas (Jurnal Pengabdian Kepada Masyarakat, 2023)
The rapid development of internet technology in the current era has changed the paradigm of traditional marketing into digital marketing using internet media, which is known as digital marketing. Digital marketing plays an important role in the success of MSME marketing because it allows analysis of new target markets, consumer behavior and product information. However, only a few MSMEs have an understanding of this digital technology-based marketing strategy. As a form of contribution to community service, students from UPN "Veteran" East Java invited and provided an understanding to the Super Klasik Feed MSME about the importance of digital marketing as a marketing strategy. The methods used include observation, interviews, digital marketing implementation, and activity evaluation. The results obtained by MSME Feed Super Klasik are an understanding of the importance of digital marketing as a marketing strategy, and students succeed in sharing knowledge through the implementation of creating Instagram social media accounts.